Pancreaticoduodenectomy following chemoradiotherapy for locally advanced adenocarcinoma of the pancreatic head. Issue 9 (10th January 2013) - Denost, Quentin; Laurent, Christophe; Adam, Jean‐Philippe; Capdepont, Maylis; Vendrely, Veronique; Collet, Denis; Sa Cunha, Antonio
Abstract Objectives The aim of this study was to assess oncological outcomes in patients treated with pancreaticoduodenectomy for advanced pancreatic head adenocarcinoma after preoperative chemoradiotherapy and to compare these with outcomes in patients treated with surgery alone. Methods From 2004 to 2009, patients treated with pancreaticoduodenectomy for pancreatic head adenocarcinoma were included in a retrospective comparative study. Patients with locally advanced adenocarcinoma were treated with preoperative chemoradiotherapy (CRT group) and were compared with those treated with surgery alone (SURG group). Results A total of 111 patients were included; these comprised 72 patients in the SURG group and 39 patients in the CRT group. The median follow‐up was 21 months. Patients in the CRT group presented with a more advanced tumoral status. Microscopic resection rates were similar in both groups, but nodal status and vascular or lymphatic emboli were lower in the CRT group. At 3 years, the SURG and CRT groups exhibited similar overall (36% and 51%, respectively) and disease‐free (35% and 37%, respectively) survival (P = 0.10). Conclusions In patients with advanced pancreatic head adenocarcinoma, a good response after preoperative chemoradiotherapy results in a survival rate similar to that in patients treated with surgery alone in whom the initial prognosis is better.